Effects of menu change on nutritional status, energy balance and food acceptance of recruits at the basic training centre in Port Dickson, Malaysia - Abdullah, Nurhazwani (2013)
Impact of basic recruit training (BT) on nutritional status is extensively studied but there are limited possible strategies to minimize the potential losses of nutritional status during BT. The research aimed to determine the effects of BT on nutritional status, energy balance, food acceptance and foodservice satisfaction during BT and subsequent menu changes was implemented after the effects were determined. There were two studies, which study 1 provided baseline assessment and study 2 was a menu changes as the intervention from results of study 1. Study 1 was a case study with 50 recruits series A for 6 months. Nutritional status measured were body weight and composition with TANITA-TBF300A, food intake with 24-hours diet recall and food weighing, physical activity status with questionnaire based on energy cost of activities, energy provided by menu and portion sizes served were calculated with Nutritionist Pro, and assessment of food acceptance and foodservice satisfaction with validated questionnaires. Study 1 showed that body weight and composition were attenuated (p<0.05) and energy intake decreased throughout BT (p<0.05) with fat as the major source of energy. Most of selected nutrients met or exceed the recommended level of nutrients except for calcium and dietary fibre. Energy requirement was high during Phase 2 BT while at Phase 3 BT, recruits showed the highest negative energy balance (p<0.05). Menu showed that the nutrients met the Recommended Level of Intakes (RNIs) for Malaysian but not the military dietary recommendation, PMAT of energy. Standard food portions served improved body weight and composition of the recruit (p<0.05). Sensory attributes was emphasized when choosing meals. Recruits rated poor foodservice satisfaction level. Study 2 was a pretest-posttest design with 75 army recruits series B that participated in the 6-months of menu changes. The effects of menu changes were examined on nutritional status, energy balance, food acceptance and foodservice satisfaction. Study 2 employed same methods as study 1 for the variables measured. Results showed that menu changes did not have significant effects on the body weight, lean body mass and total body water. However, BMI and body fat percents were significantly increased (p<0.05). The recruits consumed higher energy intake (~100 to 900 kcal) (p<0.05) and fulfilled the military dietary recommendation, PMAT for energy intake but did not meet the energy requirement of BT. Carbohydrate met the range of recommended level (55 to 70%) and fat intake met the range of fat intake (30%). Recruits attained the nutrient requirement for vitamin A, vitamin C, iron, thiamine, riboflavin, niacin, sodium and zinc. Calcium intake was close to the recommendation but dietary fibre was not sufficiently consumed. The negative energy balance was reduced throughout BT. Scores of food acceptance increased and foodservice satisfaction has improved from poor to acceptable (p<0.05) with menu changes. In conclusion, menu changes lessen the negative energy balance among the recruits. Yet, there were no significant changes of body weight and composition except for BMI and body fat. Hence, more research is warranted to establish the long term benefits of this menu approach.